Etika Komunikasi dalam Pelayanan Publik di Dinas Perpustakaan Provinsi Sumatera Selatan - Na’imatun Salsabila Rifdah; Komaruddin Komaruddin; M. Mifta Farid (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Public service is a crucial activity in government administration aimed at fulfilling community needs effectively, transparently, and accountably. This study aims to analyze communication ethics in public services at the Sumatera Selatan Provincial Library Department using the communication accommodation theory approach, which encompasses convergence, divergence, and over-accommodation. The research employs a qualitative method with data collection techniques including observation, interviews, and documentation. Informants in this study are library staff and library visitors. The results indicate that communication ethics in public services at the Sumatera Selatan Provincial Library Department are generally running quite well but still require improvements. Under communication accommodation theory, the convergence aspect that needs enhancement is nonverbal language, which remains inadequate in public services. Divergence occurs in certain situations to maintain staff professionalism, while over-accommodation is not significantly found in the service process. This study concludes that the implementation of communication ethics is quite good but still requires further improvement.